2020
DOI: 10.3390/cancers12071759
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Prognostic Factors at First Relapse in Multiple Myeloma

Abstract: The prognosis of multiple myeloma has considerably improved due to the introduction of novel agents in the upfront setting. However, the great majority of patients ultimately relapse, and choosing a salvage treatment at first relapse remains challenging. The natural history of first relapsed disease in the current era is also not well described. We retrospectively studied 300 patients with first relapsed myeloma seen between 2004 and 2019 from two institutes in Singapore. The median duration from diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…In this study, median PFS and OS of the NDMM patients were 25.0 months and 60.0 months, respectively, which were comparable to what was reported in other Asian countries [ 7 , 12 , 23 ]. Meanwhile, result from a single center study from Indonesia has shown a lower median OS at 28.0 months [ 10 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, median PFS and OS of the NDMM patients were 25.0 months and 60.0 months, respectively, which were comparable to what was reported in other Asian countries [ 7 , 12 , 23 ]. Meanwhile, result from a single center study from Indonesia has shown a lower median OS at 28.0 months [ 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, superior results were also reported in Myanmar and Singapore where more than half of their patients achieved VGPR or better although this was not observed in a study conducted in Philippines where only about a third of their patients achieved such response [22,11]. In this study, median PFS and OS of the NDMM patients were 25.0 months and 60.0 months, respectively, which were comparable to what was reported in other Asian countries [7,12,23]. Meanwhile, result from a single center study from Indonesia has shown a lower median OS at 28.0 months [10].…”
Section: Discussionsupporting
confidence: 76%
“…The distribution of patients newly diagnosed with MM ISS stage 1 (20–24%), stage 2 (38–44%), or stage 3 (33–39%) disease reflect the severity of MM at diagnosis [ 9 , 10 ]. The median duration from diagnosis to first relapse is around 22.7 months [ 11 ]. The median overall survival for patients receiving first, second, third, and fourth line of treatment (LOT) was reported to be 37.5, 19.7, 13.9, and 9.2 months, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%